Circulating plasma and exosome levels of the miR-320 family as a non-invasive biomarker for methamphetamine use disorder - Xu, Wenjin; Hong, Qingxiao; Zhou, Yun; Chen, Xiaoyu; Li, Longhui; Wang, Majie; Chen, Weisheng; Xie, Xiaohu; Zhuang, Dingding; Lai, Miaojun; Zhou, Wenhua; Liu, Huifen (Frontiers in Psychiatry, 2023)
The neurobiological mechanism underlying methamphetamine (MA) use disorder was still unclear, and no specific biomarker exists for clinical diagnosis of this disorder. Recent studies have demonstrated that microRNAs (miRNAs) are involved in the pathological process of MA addiction. The purpose of this study was to identify novel miRNAs for the diagnosis biomarkers of MA user disorder. First, members of the miR-320 family, including miR-320a-3p, miR-320b, and miR-320c, were screened and analyzed in the circulating plasma and exosomes by microarray and sequencing. Secondly, plasma miR-320 was quantified by real-time quantitative reverse transcription polymerase chain reaction (RT-qPCR) in eighty-two MA patients and fifty age-gender-matched healthy controls. Meanwhile, we also analyzed exosomal miR-320 expression in thirty-nine MA patients and twenty-one age-matched healthy controls. Furthermore, the diagnostic power was evaluated using the area under the curve (AUC) of the receiver operating characteristic (ROC) curve. The expression of miR-320 significantly increased in plasma and exosomes of MA patients compared with healthy controls. The AUC of the ROC curves of miR-320 in plasma and exosomes of MA patients were 0.751 and 0.962, respectively. And the sensitivities of miR-320 were 0.900 and 0.846, respectively, whereas the specificities of miR-320 were 0.537 and 0.952, respectively, in plasma and exosomes in MA patients. And the increased plasma miR-320 was positively correlated with cigarette smoking, age of onset, and daily use of MA in MA patients. Finally, cardiovascular disease, synaptic plasticity, and neuroinflammation were predicted to be the target pathways related to miR-320. Taken together, our findings indicated that plasma and exosomal miR-320 might be used as a potential blood-based biomarker for diagnosing MA use disorder.